560 Alcohol levels and injury related mortality. (1st September 2016) - O'Brien, Ms Aine; Molcho, Michal
Abstract : Background: Limited data on injury mortality were traditionally collected using death certificates. Coroners' inquest reports offer a richer source of injury mortality data; collating information from multiple sources (including police reports, witness statements, coronial autopsy and forensic pathologist post-mortem and toxicology examinations). These reports provide information on the manner and mechanism of injury, the presence of alcohol and drugs, a detailed description of injuries sustained and a narrative of the circumstances resulting in death. Methods: This study reviewed 722 coroners' inquest investigation reports of injury related death between 2006 and 2010 in the West of Ireland, including coronial and forensic pathologist post-mortem and toxicology examination results. Alcohol levels were measured in blood and urine and included in toxicology results. This paper focuses on the presence of alcohol in various injury related fatalities. Results: Alcohol was detected in 54.2% of cases (78% male and 22% female), most commonly among 0–44 year-olds (49%). Where alcohol was present, it was most frequently at a level greater than 200 mg/100 ml. Alcohol was present in 41% of unintentional fatalities, 19% of intentional fatalities, and 40% of undetermined intent fatalities. Alcohol was detected in 40% of asphyxiated fatalities, consisting of 49.7% hanging and 41.4% of drowning fatalities. Blood alcohol levels >200 mg/100 ml were found in 39% of the drowning fatalities, while levels <20mg/100 ml were detected in 30% of the hanging fatalities. Conclusions: Alcohol is a major contributor to injury related mortality in the West of Ireland, particularly among young people, with young men especially vulnerable. It is evident that injury fatalities resulting from asphyxiation are commonly associated with alcohol, where the level of alcohol detected varies across types of injury fatality.